2021
DOI: 10.1021/acsnano.0c10144
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bioaugmentation of Biomacromolecules and Living Organisms for Biomedical Applications

Abstract: The synergistic union of nanomaterials with biomaterials has revolutionized synthetic chemistry, enabling the creation of nanomaterial-based biohybrids with distinct properties for biomedical applications. This class of materials has drawn significant scientific interest from the perspective of functional extension via controllable coupling of synthetic and biomaterial components, resulting in enhancement of the chemical, physical, and biological properties of the obtained biohybrids. In this review, we highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 242 publications
0
40
0
Order By: Relevance
“…They can act as central binding sites for nucleic acids, antigenic proteins, and cells, protecting these biomolecules from external stressors and permitting delivery to endosomes/lysosomes. [ 98 ] After releasing encapsulated biomolecules, CaP nanoparticles are decomposed due to the change in pH of the environment from neutral into acidic during cellular uptake, which makes them ideal vehicles. It was found that these nanoparticles are valuable and easily biodegradable adjuvants for DNA vaccines and mucosal immunity.…”
Section: Development Of Nano‐based Vaccinesmentioning
confidence: 99%
“…They can act as central binding sites for nucleic acids, antigenic proteins, and cells, protecting these biomolecules from external stressors and permitting delivery to endosomes/lysosomes. [ 98 ] After releasing encapsulated biomolecules, CaP nanoparticles are decomposed due to the change in pH of the environment from neutral into acidic during cellular uptake, which makes them ideal vehicles. It was found that these nanoparticles are valuable and easily biodegradable adjuvants for DNA vaccines and mucosal immunity.…”
Section: Development Of Nano‐based Vaccinesmentioning
confidence: 99%
“…In particular, many novel materials have emerged and are functionalized with “smart” properties in that they can sense and respond to external environmental stimuli [ 1 ]. With the development in multidisciplinary aspects, smart materials have been widely employed in biosensing, drug delivery, tissue engineering, wearable devices, etc [ [2] , [3] , [4] , [5] , [6] , [7] ]. Smart materials are generally composed of various active components, among which the living cells are extraordinarily attractive since they could respond to even weak stimuli and produce highly complex biological activities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Engineering living cells with synthetic materials is emerging as a powerful strategy for biotechnology innovation. [1][2][3][4][5][6][7][8][9][10][11][12] Engineered cells with modulated or augmented cellular functions have applications in various elds, ranging from therapeutical agents to living so materials. [13][14][15][16][17][18][19] For example, cell surface engineering modulating communications between the cell and its surrounding environment has led to unique applications such as selective cell-based therapy, [20][21][22] targeting drug delivery systems, [23][24][25][26] universal blood, 27,28 and cell cryopreservation.…”
Section: Introductionmentioning
confidence: 99%